The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis